Peningkatan Kemampuan Menulis Teks Drama dengan Mengadopsi Novel pada Kelas XI-10 SMAN 2 Kota Semarang - Yhoga, Yhoga Pratama; Asropah,; Agus Wismanto,; Watini, (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve the ability to write drama texts in class XI-10 SMAN 2 Kota Semarang in the Indonesian Language subject. This study was motivated by the low ability of students in writing drama texts, especially in developing stories in drama texts. The research method used was Classroom Action Research (CAR) which was carried out for two cycles. The subjects of this study were all students of class XI-10 SMAN 2 Kota Semarang in the 2024/2025 academic year. Data collection was carried out through tests and observations. Qualitative data were analyzed using scoring guidelines based on assessment instruments, while quantitative data were processed using descriptive statistics to measure the improvement in the ability to write drama texts. The results of the study showed a gradual increase in the results of the pretest, cycle I, and cycle II. With these results, it can be said that improving the writing of drama texts by adopting novels is effective in learning the Indonesian Language course on drama text material.